Pol točke za MOK - Prajnc, Vojko (Šport (Ljubljana), 2017)
It's hard to find sport which is divided in so many schools, styles, groups and federations and also passed so many disparities and conflicts as karate. Since Indian priest Boddhidarma eliminated from the west India to a few thousand kilometers long journey to China and share first knowledge the history of karate is divided into five phases of development: Chinese sources (from around 2600 BC), okinawan period (from 1372), Japanese period (from 1920), the beginnings of competitive sports (from 1950) and the period of the Olympic karate. First karate clubs in Slovenia were founded in Krško (1967) and Ravne na Koroškem (1968). Efforts for karate becoming an Olympic sport, are big and longterm. Efforts to include karate in the company of Olympic sports have nevertheless continued and in June 2016 the International Olympic Committee messaged that karate is going to be one of the Olympic sports at the Summer Olympics in 2020, which will be held in Japan. Excatly fifty years after the first official World Championship was organized in Tokyo in remarkable %dome of the martial arts% Budokan in Tokyo karate will symbolically and actually unite under same roof.
Keywords: Boddhidarma; Budokan; karate; olimpijski športi; olympic sport; sport; šport; vpliv